1988
DOI: 10.1152/jappl.1988.65.1.401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epinephrine on neutrophil kinetics in rabbit lungs

Abstract: The effect of epinephrine on neutrophil (PMN) kinetics in rabbit lungs was evaluated by measuring the retention of radiolabeled PMN's in the lung, the exchange rate between the marginated and circulating pools of PMN's, and the erythrocyte (RBC) transit time. Epinephrine treatment decreased RBC transit times and increased exchange rates in the regions with the shortest transit times but did not change the pulmonary recovery of radiolabeled PMN's. When regions of similar RBC transit time were compared, epinephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Instead, it elicits neutrophilia by promoting neutrophil release from the marginated pool present in the lung and preventing neutrophil circulation back to the BM ( Devi et al, 2013 ). This demargination is likely to be caused by increased neutrophil blood velocities and decreased endothelium–neutrophil interactions ( Doerschuk et al, 1988 ). A recent study also suggested that autophagy plays a role in G-CSF–elicited stem cell mobilization ( Leveque-El Mouttie et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it elicits neutrophilia by promoting neutrophil release from the marginated pool present in the lung and preventing neutrophil circulation back to the BM ( Devi et al, 2013 ). This demargination is likely to be caused by increased neutrophil blood velocities and decreased endothelium–neutrophil interactions ( Doerschuk et al, 1988 ). A recent study also suggested that autophagy plays a role in G-CSF–elicited stem cell mobilization ( Leveque-El Mouttie et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Native catecholamines, like adrenaline, routinely increase the number of circulating granulocytes in both man (Strader et al 1989) and experimental animals (Doerschuk et a/. 1988), this effect may not necessarily, however, be due to decreased granulocyte adhesion to the vascular wall (Doerschuk et al 1988). Consequently, the mechanism causing the antiaggregatory effect found for terbutaline is uncertain, and not necessarily a P,-agonists mediated one.…”
Section: Discussionmentioning
confidence: 99%
“…Radiolabelled granulocytes given in conjunction with labelled erythrocytes for measuring erythrocyte transit time and regional pulmonary blood volume, with radioiodinated albumin for measuring pulmonary haematocrit and with labelled denatured protein aggregates for measuring regional pulmonary blood flow, have been used experimentally to quantify pulmonary granulocyte pooling [32, [41][42][43]. An indicator dilution technique used by Hogg's group involves rapid sampling of aortic blood immediately after central venous injection of differentially labelled granulocytes and erythrocytes [19, 39, 43, 441.…”
Section: Radiolabelled Blood Cellsmentioning
confidence: 99%